To solve the equation \(2x - 72 = 32\), we can follow these steps:
- First, add 72 to both sides of the equation:
\[ 2x - 72 + 72 = 32 + 72 \]
This simplifies to:
\[ 2x = 104 \]
- Next, divide both sides by 2:
\[ \frac{2x}{2} = \frac{104}{2} \]
This gives us:
\[ x = 52 \]
Thus, the solution to the equation \(2x - 72 = 32\) is \(x = 52\).
Now, let’s compare this with the options you provided:
- \(x = 7 \pm 32\) (Results in \(x = 39\) or \(x = -25\))
- \(±65\) (This does not apply to the equation.)
- \(x = 3\) and \(x = 11\) (These are not solutions.)
- \(x = -1\) and \(x = 15\) (These are also not solutions.)
None of the options match the correct solution \(x = 52\).